TASAWUF AKHLAKI - Sahla Mardhiah; Khalilurrahman Khalilurrahman; Anshari Anshari (Jurnal Shaf, 2026)
This article discusses the concept of moral Sufism (tasawuf akhlaki) and tazkiyatun nafs as an ethical spiritual approach to addressing the moral crisis in modern society. The increasing phenomena of individualism, hedonism, and the weakening of moral values indicate that technological and intellectual progress is not always accompanied by the development of human character. Therefore, this research aims to analyze the conceptual framework of moral Sufism and the process of soul purification within the tradition of classical Islamic thought. This study employs a qualitative descriptive method using a library research approach by examining the works of classical Sufi scholars such as Hasan al-Basri, Al-Ghazali, Al-Qusyairi, and Al-Muhasibi. The findings show that moral Sufism emphasizes character formation through the stages of takhalli, tahalli, and tajalli, along with the cultivation of virtues such as repentance, patience, asceticism, tawakkal, mahabbah, and ridha. These concepts remain relevant as an ethical and spiritual framework for strengthening moral character and inner balance in contemporary life.